PENERAPAN PEMBELAJARAN SAINS DAN MATEMATIKA UNTUK MEMBANGUN MERDEKA BELAJAR ANAK USIA DINI - Neni Mulya; Jatmiko, Agus; Wijaya Kuswanto, Cahniyo; Viyantini Kuswanto , Anggil (UHN I GUSTI BAGUS SUGRIWA DENPASAR, 2024)
The independent curriculum was initiated as part of the solution to improve teaching and learning in Indonesia. This independent curriculum is closely related to the concept of independent learning which provides flexibility in learning for students. Science and math learning is important to be applied through fun games so that children are always happy and not constrained in learning at school according to the age of the learners playing while learning. This research uses a descriptive qualitative method with case studies used to collect data. The results of the findings in the field show that there are three findings, namely the first Science and Mathematics learning is simpler and more in-depth designed in a fun way and method, the second is more independent The concept that is carried out with science and mathematics learning provides space and time for students to explore their knowledge abilities, and the third is more relevant and interactive to strengthen meaningful play activities as a learning process. The application of Science and Mathematics Learning can be done by conducting assessments with anecdotal notes and work results.